2004
DOI: 10.1002/hep.20284
|View full text |Cite
|
Sign up to set email alerts
|

Ligation versus propranolol for the primary prophylaxis of variceal bleeding in cirrhosis†

Abstract: In this randomized controlled multicenter trial, we compared endoscopic variceal banding ligation (VBL) with propranolol (PPL) for primary prophylaxis of variceal bleeding. One hundred fifty-two cirrhotic patients with 2 or more esophageal varices (diameter >5 mm) without prior bleeding were randomized to VBL (n ‫؍‬ 75) or PPL (n ‫؍‬ 77). The groups were well matched with respect to baseline characteristics (age 56 ؎ 10 years, alcoholic etiology 51%, Child-Pugh score 7.2 ؎ 1.8). The mean follow-up was 34 ؎ 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
194
4
13

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(215 citation statements)
references
References 32 publications
4
194
4
13
Order By: Relevance
“…The first variceal bleeding and upper gastrointestinal bleeding rates were even slightly higher in patients receiving banding ligation as well as nadolol. The controlled trial with the largest sample size up to now, conducted by Schepke et al, 11 showed that variceal bleeding was 25% in the ligation group and 29% in the propranolol group. Compared with previous trials, our current figures of variceal bleed and upper gastrointestinal bleed in both groups were reasonable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first variceal bleeding and upper gastrointestinal bleeding rates were even slightly higher in patients receiving banding ligation as well as nadolol. The controlled trial with the largest sample size up to now, conducted by Schepke et al, 11 showed that variceal bleeding was 25% in the ligation group and 29% in the propranolol group. Compared with previous trials, our current figures of variceal bleed and upper gastrointestinal bleed in both groups were reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous trials, our current figures of variceal bleed and upper gastrointestinal bleed in both groups were reasonable. [9][10][11][12] A total of 321 patients (70%) were excluded from the study. The majority of these excluded patients were due to the presence of hepatocellular carcinoma and old age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of VBL for primary prophylaxis that include patients with high-risk esophageal varices have shown that VBL significantly reduces the risk of first variceal bleeding and that serious adverse effects are uncommon [53][54][55][56][57]. A meta-analysis of five studies of VBL versus placebo suggested that VBL reduces the risk of first variceal bleed, bleeding-related mortality, and overall mortality [58].…”
Section: Recommendationsmentioning
confidence: 99%
“…Various published randomized trials comparing the efficacy and safety of VBL and b-blockers in primary prophylaxis exist [53][54][55][56][57][63][64][65][66][67]. A recent meta-analysis suggests that VBL has greater efficacy in preventing initial bleeding with a 34% relative risk reduction than do b-blockers.…”
Section: Recommendationsmentioning
confidence: 99%